EDUCATIONAL GAMES ORGANIZED IN 3RD-4TH GRADE MOTHER TONGUE CLASSES AND PECULIARITIES OF THEIR USE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
In this article, educational games used in 3rd-4th grade mother tongue lessons, their content, effectiveness and methodology are analyzed based on specific sources